Implementasi Kebijakan Pemberdayaan Masyarakat melalui Budidaya Kopi di Desa Sobo - Arif Setia Budi (Lembaga Yasin AlSys, 2026)
Village community empowerment based on local potential is an important strategy for enhancing self-reliance and economic resilience, including in Sobo Village, Pacitan Regency, which has fertile land but whose residents remain dependent on rainfed agriculture and seasonal livestock farming. This study aims to describe the implementation of community empowerment policies through coffee cultivation as an alternative livelihood diversification option. It employs a descriptive qualitative approach with a case study design, using data collected through observation, interviews, and documentation involving village officials, students of the Kuliah Kerja Nyata (KKN) program from ISIMU, and beneficiary community members. The findings show that the distribution of coffee seedlings and the provision of technical assistance fostered active community participation, encouraged the productive use of home yards, and opened opportunities for long-term income improvement. Although doubts remain regarding short-term economic benefits, coffee cultivation has potential as an empowerment policy instrument that supports the strengthening of village economic resilience. These findings underscore the importance of optimizing local potential and reinforcing empowerment policies as the basis for sustainable village economic development.